Young Russian adults' attitudes towards the potential use of robots in hotels. (November 2018) - Ivanov, Stanislav; Webster, Craig; Garenko, Aleksandra
Abstract: Robots are increasingly discussed in academic literature as well as the popular media since they are becoming more usual in industry. The increased use of robots will meet with practical issues with regards to adoption in industry as well as resistance from customers and those working in the industry. This work explores data from a 2016–2017 survey of Russian consumers to determine how young Russian adults perceive the use of robots in hotels, showing which service-oriented tasks that Russian consumers find to be the most agreeable to be done by robots and which ones they are more likely to want humans to continue doing. The findings reveal that those who are most supportive of having robots in hotels tend to be Muscovites, males, and those already supportive of the use of service industries in general. In addition, there are noteworthy differences in how males and females perceive of the acceptability of different types of tasks that robots may do in hotels. Highlights: The attitudes of young Russian adults towards robots in hotels is investigated. Robots are accepted as information providers, for transporting goods, payments, not as guards or for massages. Men consider robots as more acceptable than women. Robots' advantages, social skills, and robotic service experience influence positively attitudes. Positive attitude towards service robots linked to higher acceptance of robots in hotels.